2000
DOI: 10.1164/ajrccm.162.5.9906096
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Elevation of Matrix Metalloproteinase Activity in Idiopathic Interstitial Pneumonias

Abstract: Destruction of subepithelial basement membrane is a key event in the pathogenesis of idiopathic pulmonary fibrosis (IPF). To evaluate the role of matrix metalloproteinases (MMPs) in parenchymal remodeling in idiopathic interstitial pneumonia (IIP), we studied MMP-2 and -9 activity, in bronchoalveolar lavage fluid (BALF) by zymography and the expression of MMP-2 and -9 and TIMP-2 in lung tissue by immunohistochemistry. BALF and lung tissues were collected from 26 patients with usual interstitial pneumonia (IPF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
153
1
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(176 citation statements)
references
References 24 publications
(32 reference statements)
13
153
1
8
Order By: Relevance
“…been implicated in this disease process. 40 Using a similar experimental approach to that of the present study, Zuo et al 11 demonstrated enhanced expression of MMP-7 (matrilysin) mRNA in the lungs of patients with IPF and showed that that genetic deficiency of MMP-7 in mice conferred protection against bleomycin-induced pulmonary fibrosis. Thus, although the precise mechanism or mechanisms by which MMPs are involved in pulmonary fibrosis remain to be clarified, these studies provide support for the notion that MMPs play a crucial role in the pathobiology of IPF.…”
Section: Discussionsupporting
confidence: 59%
“…been implicated in this disease process. 40 Using a similar experimental approach to that of the present study, Zuo et al 11 demonstrated enhanced expression of MMP-7 (matrilysin) mRNA in the lungs of patients with IPF and showed that that genetic deficiency of MMP-7 in mice conferred protection against bleomycin-induced pulmonary fibrosis. Thus, although the precise mechanism or mechanisms by which MMPs are involved in pulmonary fibrosis remain to be clarified, these studies provide support for the notion that MMPs play a crucial role in the pathobiology of IPF.…”
Section: Discussionsupporting
confidence: 59%
“…When immunohistochemistry was considered, the main locus of the MMP-2 was fibroblasts composed of interstitial tissues. In previous reports, the concentration of MMP-2 in the fibrotic tissues was found to be correlated with the degree of progression of pulmonary fibrosis [6] [12], which is consistent with the results of our study. Conversely, MMP-9 was observed in the neutrophils and lymphocytes of patients with IIP.…”
Section: Discussionsupporting
confidence: 93%
“…MMP's -1, 2, 8 and 9 have also been demonstrated to be elevated in asthmatic airways albeit to a lesser extent than in COPD [20]. Increased expression of MMPs-8, 9 and 7 has been demonstrated in the fibrosing diseases, IPF and pulmonary sarcoidosis [21][22][23][24].…”
Section: Proteases and The Lungmentioning
confidence: 99%